Enhancement of stripping technique for Copper(II) detection in water sample using N,N'-bis(2-hydroxy-4-methoxyacetophenone)ethylenediamine (BME) - Syaza Azhari; Rahmalan Ahamad; Farediah Ahmad (Penerbit UTM Press, 2024)
Indexed by MyCite